A low band gap n-type polymer based on dithienosilole and naphthalene diimide for all-polymer solar cells application. (20th April 2015) - Geng, Yanfang; Huang, Jianming; Tajima, Keisuke; Zeng, Qingdao; Zhou, Erjun
Abstract: Naphthalene diimide (NDI) and dithienosilole (DTS) have been well known building blocks for photovoltaic materials. Herein a solution-processable low band gap conjugated polymer, PDTS-NDI, consisting of NDI moiety and DTS unit was synthesized as a new n-type material. The polymer has two broad absorption bands in the range of 300–500 nm and 500–950 nm. Power conversion efficiencies (PCEs) of the polymer blend solar cells in the range of 0.13–0.70% were obtained under simulated AM 1.5, 100 mW/cm 2 irradiation, where two polymers with conjugated side chains, PT1 and TTV2, were used as p-type material. For the combination of TTV2 and PDTS-NDI, it was further optimized to give a PCE of 1.19% by adding 1, 8-diiodooctane (DIO) as solvent additive, suggesting a potential of PDTS-NDI polymer for the photovoltaic application. Graphical abstract: Highlights: An n-type low band gap conjugated polymer, PDTS-NDI, was synthesized. The polymer has two broad absorption bands in the range of 300–500 nm and 500–950 nm. The PCE of TTV2:PDTS-NDI blend solar cell reached 1.19% with DIO as solvent additive.